Status Kepemilikan Saham Hasil Pembatalan Penggabungan Perseroan Terbatas oleh Komisi Pengawas Persaingan Usaha - Dian Karina Fitri; Sihabudin Sihabudin; Bambang Winarno (Jurnal Cakrawala Hukum, 2019)
Limited Liability Company is a legal action carried out by one or more companies to merge with other existing companies which then results in the assets and liabilities of the company which merges itself due to the law to the company that receives the merger and subsequently the legal entity status those who join will end because ofthe law. This study discusses the status of share ownership resulting from the cancellation of the merger of Limited Liability Company. The purpose of this study is to analyze the absence of legal rules regarding share ownership status after cancellation by the Business Competition Supervisory Commission (hereinafter referred to as KPPU). The researcher used the normative jurisdiction method. The approach used is the legislative approach. Legal materials used are primary and secondary legal materials. Legal material collection techniques used through library studies. The analysis technique used is deductive logic, which draws conclusions from the general to the specific. The results of the study indicate that there is a legal vacuum in share ownership status related to the cancellation of the merger of Limited Liability Company. Because the emptiness causes legal uncertainty and huge consequences for the business world.How to cite item: Fitri, D., Sihabudin, S., Winarno, B. (2019). Status Kepemilikan Saham Hasil Pembatalan Penggabungan Perseroan Terbatas oleh Komisi Pengawas Persaingan Usaha. Jurnal Cakrawala Hukum, 10(1), 9-17. doi:https://doi.org/10.26905/idjch.v10i1.2609